2015
DOI: 10.1055/s-0035-1550338
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Bearings versus Rotating Platforms in Total Knee Arthroplasty

Abstract: Rotating platforms were introduced as an alternative to fixed bearings in hopes of providing more natural kinematics and improved clinical outcomes. In-vitro wear studies showed significantly less wear with rotating platforms as opposed to fixed-bearing designs. Kinematic follow-up studies showed significantly improved axial rotation with rotating-platform knees. However, these benefits have failed to translate into improved clinical outcomes or survivorship. This article reviews our institution's experience, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Recently, the in vitro reduction of torque forces, demonstrated when using a rotating platform, has encouraged some surgeons to use this implant in younger patients with higher impact forces, and in revision operations using constrained implants for poor bone stock (White et al. 2015 , Small et al. 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the in vitro reduction of torque forces, demonstrated when using a rotating platform, has encouraged some surgeons to use this implant in younger patients with higher impact forces, and in revision operations using constrained implants for poor bone stock (White et al. 2015 , Small et al. 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that even if backside wear was included, RP wear would not exceed FB wear. 40 In fact, some previous retrieval 27 and experimental 28 studies found lower total, and even backside, wear rates for RP than FB implants.…”
Section: Discussionmentioning
confidence: 97%
“…Mobile-bearing systems such as rotating-platform TKAs were aimed at correcting these deficiencies. They were originally developed to provide dual-surface articulation that uncouples axial and translational forces of the knee [1]. Uncoupling of these forces was thought to reduce loosening rates of fixed-bearing designs, provide more normal kinematics, and increase survivorship [1].…”
Section: Discussionmentioning
confidence: 99%
“…They were originally developed to provide dual-surface articulation that uncouples axial and translational forces of the knee [1]. Uncoupling of these forces was thought to reduce loosening rates of fixed-bearing designs, provide more normal kinematics, and increase survivorship [1]. Although kinematic motion analysis supports the use of mobile-bearing TKAs, clinical studies have failed to report increased efficacy of mobile-bearing TKAs vs. fixed-bearing systems [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation